Cost-effectiveness analysis of implementing an antimicrobial stewardship program in critical care units. (3rd June 2017) - Ruiz-Ramos, Jesus; Frasquet, Juan; Romá, Eva; Poveda-Andres, Jose Luis; Salavert-Leti, Miguel; Castellanos, Alvaro; Ramirez, Paula
Abstract: Aims: To evaluate the cost-effectiveness of antimicrobial stewardship (AS) program implementation focused on critical care units based on assumptions for the Spanish setting. Materials and methods: A decision model comparing costs and outcomes of sepsis, community-acquired pneumonia, and nosocomial infections (including catheter-related bacteremia, urinary tract infection, and ventilator-associated pneumonia) in critical care units with or without an AS was designed. Model variables and costs, along with their distributions, were obtained from the literature. The study was performed from the Spanish National Health System (NHS) perspective, including only direct costs. The Incremental Cost-Effectiveness Ratio (ICER) was analysed regarding the ability of the program to reduce multi-drug resistant bacteria. Uncertainty in ICERs was evaluated with probabilistic sensitivity analyses. Results: In the short-term, implementing an AS reduces the consumption of antimicrobials with a net benefit of €71, 738. In the long-term, the maintenance of the program involves an additional cost to the system of €107, 569. Cost per avoided resistance was €7, 342, and cost-per-life-years gained (LYG) was €9, 788. Results from the probabilistic sensitivity analysis showed that there was a more than 90% likelihood that an AS would be cost-effective at a level of €8, 000 per LYG. Limitations: Wide variability of economic results obtained from the implementation of this type of AS program and short information on their impact on patient evolution and any resistance avoided. Conclusions: Implementing an AS focusing on critical care patients is a long-term cost-effective tool. Implementation costs are amortized by reducing antimicrobial consumption to prevent infection by multidrug-resistant pathogens.